EFFECT OF USING THE TITHONIA DIVERSIFOLIA LEAF MEAL IN THE DIET FORMULATION ON PERFORMANCE OF BROILER CHICKENS - Apri Dandi; Jiyanto Jiyanto; Pajri Anwar (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to determine the effect of Titonia Leaf Meal (Tithonia Diversifolia) on body weight gain, feed consumption and feed conversion of ratio of broiler. The research were carried out for 35 days from July to August 2019. This research is located in farm have Mr Sudirman in Sungai Jering Village, Central Kuantan District Kuantan Singingi Regency. The observed parameter was body weight gain, feed consumption and feed conversion of ratio. This study used a completely randomized design (CRD) method, with 5 treatments and 4 replications. The treatment given were: R0 = diet containing 0% TLM; R1 = diet containing 4% TLM; R2 = diet containing 6% TLM; R3 = diet containing 8% TLM; R4 = diet containing 10% TLM. The results showed the addition of TLM significantly affected diet consumption and not significantly affect body weight gain and feed conversion of ratio. Titonia Leaf Meal can be use 6% in the diet of broiler.